بلاغة الحمل على المعنى في القرآن الكريم {التذكير والتأنيث} أنموذجا -دراسة في السبع الطوال - مسعودي, عبد الغني (University of Eloued جامعة الجزائر, 2020)
"هذا البحث بعنوان: ""بلاغة الحمل على المعنى في القرآن الكريم - التذكير والتأنيث أنموذجا - دراسة في السبع الطوال"". وهو يطرح إشكالية: العدول عن المطابقة في التذكير والتأنيث في القرآن الكريم، عللها النحوية وأسرارها البلاغية في ضوء الحمل على المعنى. ولمعالجة هذه الإشكالية: قمنا بالتعريف بالحمل على المعنى في العربية، ببيان مفهومه، وأهم قواعده وصوره وأقسامه، وأثره في جبر المعنى. كما استقصينا الشواهد التي تمثل العدول عن المطابقة في التذكير والتأنيث في السبع الطوال، وتخريجاتها النحوية، وبعض أسرارها البلاغية. وقد توصل البحث إلى عدة نتائج أهمها: - الحمل على المعنى باب شاسع في العربية، وسنة من سنن العرب في كلامها، وبه جاء القرآن الكريم. - تخريج العدول عن المطابقة في القرآن الكريم يشترك فيه القياس النحوي مع الحمل على المعنى. - الحمل على المعنى باب من أبواب اتساع الدلالة وثرائها، بما فيه من أسرار بلاغية ونكت معنوية."This research is entitled: ""The Implied of the Meaning in the Holy Qur’an - Masculine and Feminization as a Model - A Study in the Long Seven. It poses a problem of: Displacement in the Masculine and Feminization in the Holy Qur’an its grammar existences and Rhetorical secrets about The Implied of the Meaning. To address this problem: We defined the Implied of the Meaning in the Arabic language: by Explaining its definition, its rules, its types its divisions and its effect in the Correct of meaning. as such We investigated the examples that represent displacement in the Masculine and Feminization in the Long Seven and its grammar Explanations and some Rhetorical secrets. We have reached several results, the most important of which are: - The Implied of the Meaning is a great section in Arabic, and one of the ways of the Arabs in her speaking, It was brought by the Holy Qur’an. - The grammar explanations of displacement in the Holy Qur’an It is shared with grammar and the Implied of the Meaning. - The Implied of the Meaning is a section of the significance and its wealth with its rhetorical secrets and moral benefits.
مذكرة ماستر تخصص لغة ودراسات قرانية
Keywords: الحمل - المعنى - التخريج البلاغي - التخريج النحوي; Meaning - Implied - rhetorical secrets